LAYANAN BIMBINGAN KELOMPOK SECARA ONLINE TERHADAP KEMATANGAN KARIER DENGAN MENGGUNAKAN TEKNIK DISKUSI PADA SISWA KELAS XII DI MADRASAH ALIYAH ASSAKINAH - Amanda Anhar Nurlatifah; Euis Eti Rohaeti; Williya Novianti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Career maturity is the ability of students to make decisions, plan and choose jobs for themselves, especially in the era of the industrial revolution 4.0 which competes with technological advances. Online group guidance using discussion techniques is an approach to guidance and counseling provided by counselors or BK teachers to counselees or students by exchanging ideas and information between group members in which there are activities to share information about careers, discussions and online questions and answers. which is done in groups by paying attention to the principles of group guidance. The purpose of this study was to determine the application of online group guidance services for class XII students at Madrasah Aliyah Assakinah. Qualitative descriptive with triangulation research design is the method used in this study. The subjects in this study were ten students of class XII at Madrasah Aliyah Assakinah. Based on the results of interviews, observations and documentation studies, there are differences in students before being given online group guidance services on career maturity using discussion techniques. Students who have been given online group guidance services on career maturity using discussion techniques show better career maturity. Keywords: Career Mtarurity, Discussion Technique, Group Conseling